Computerized Search for the Invariant Structural Elements of Znamennyi Chant - Bakhmutova, Irina V.; Gusev, Vladimir D.; Titkova, Tatyana N. (Music Scholarship / Problemy Muzykal'noj Nauki, 2011)
The article provides the description of the system of neumatic structural units – ichos-specifi c invariants (II) found in a given selection of hymns. These are repeated unambiguouslyinterpretable neumatic chains of different lengths in particular glases (ichoses) (in some sense, they are “isles of reliability”). On the basis of three dvoyeznamenniks (hymnals, in which the texts are presented in notes and neumes in parallel) the sets of II were constructed, their characteristics studied, the cover estimations by these chains of the control group of texts (without special sign-markings – pometas) has been received. Dictionaries may be applied in any methods of deciphering the neumatic notation without pometas. Keywords: dvoyeznamenniks, hymns, neumes, pometas, interglas (ichos-specifi c) invariants, deciphering of the neumes notation without pomets